Efektivitas program pendidikan anti korupsi di perguruan tinggi indonesia - ELLYANI, ANYA DEWI NUR (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the effectiveness of anti-corruption education programs in higher education institutions in Indonesia in shaping students’ integrity. Anti-corruption education is considered a strategic preventive effort to reduce corrupt practices through the cultivation of values such as honesty, responsibility, and transparency. This research employs a qualitative approach using a literature review method from various scientific sources, as well as an analysis of program implementation in several universities.The results indicate that the integration of anti-corruption education into both academic and non-academic activities can enhance students’ awareness, understanding, and attitudes toward the importance of integrity. However, the effectiveness of the program still faces several challenges, including the lack of innovative teaching methods, limited lecturer training and competence, and the suboptimal application of anti-corruption values in students’ daily lives.Therefore, it is necessary to strengthen more contextual, interactive, and participatory learning strategies, along with continuous institutional support, to maximize the impact of anti-corruption education programs in developing a generation with strong integrity.